Balloon pulmonary angioplasty for inoperable patients with chronic thromboembolic pulmonary hypertension: the initial German experience. Issue 6 (8th June 2017) - Olsson, Karen M.; Wiedenroth, Christoph B.; Kamp, Jan-Christopher; Breithecker, Andreas; Fuge, Jan; Krombach, Gabriele A.; Haas, Moritz; Hamm, Christian; Kramm, Thorsten; Guth, Stefan; Ghofrani, Hossein Ardeschir; Hinrichs, Jan B.; et al.
Balloon pulmonary angioplasty (BPA) is an emerging treatment for patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). We report on a prospective series of 56 consecutive patients who underwent 266 BPA interventions (median, five per patient) at two German institutions. All patients underwent a comprehensive diagnostic work-up including right heart catheterisation at baseline and 24 weeks after their last intervention. BPA resulted in improvements in WHO functional class, 6 min walk distance (mean change, +33 m), right ventricular function and haemodynamics, including a decline in mean pulmonary artery pressure by 18% and in pulmonary vascular resistance by 26%. Procedure-related adverse events occurred in 9.4% of the interventions. The most common complications were related to pulmonary vascular injury and consecutive pulmonary bleeding. Most of these events were asymptomatic and self-limiting, but one patient died from pulmonary bleeding, resulting in a mortality rate of 1.8%. BPA resulted in haemodynamic and clinical improvements but was also associated with a considerable number of complications, including one fatal pulmonary bleeding. As the effects of BPA on survival are unknown, randomised controlled outcome trials comparing BPA with approved medical therapies in patients with inoperable CTEPH are required to allow for appropriate risk–benefit assessments. BPA improves haemodynamics and exercise capacity in patients with inoperable CTEPH but complications are not uncommon http://ow.ly/mMYY30b1rch